Endovascular Treatment of Vertebral Artery Dissecting Aneurysms using Stents - Naito, I. (Centauro S.r.l., 2004)
We report on five patients who were treated by stent-assisted coil embolization to preserve the patency of the parent artery. Three patients presented with subarachnoid haemorrhage and two with ischemic symptoms. Four patients were treated with stenting and then followed by coil embolization of the aneurysmal dilatation, and the remaining patient with stenting alone because the aneurysmal dilatation was too small to insert coils. Complete obliteration of the aneurysm was achieved in three patients, but in one patient an aneurysmal rupture occurred during the insertion of the first coil and a parent artery occlusion was therefore performed. In the one patient treated with stenting alone, a small aneurysmal dilatation remained patent, but complete obliteration was confirmed by the follow-up angiography. Subsequent subarachnoid haemorrhage was not observed in any of the patients. Four of them achieved a good recovery, but one patient suffered severe disability due to the aneurysmal rupture during the procedure. Parent artery occlusion remains the treatment of choice. Stent-assisted coil embolization has a higher risk of rupture than does the parent artery occlusion during the procedure. Furthermore, recanalization or subsequent subarachnoid haemorrhage is more likely to occur in a stent-assisted coil embolization after the procedure. However, this procedure, which can maintain the patency of the parent artery, will become an alternative for patients who are at a high risk of developing ischemic symptoms in parent artery occlusions.